Evaluation of the Effectiveness of Professional Education Programs for Teachers - Iskandar; Said Rahmat Aulia; Irsan (el-Nizami : Jurnal Manajemen Pendidikan, 2024)
The purpose of this research is to determine how effective the professional education program is for elementary school teachers Improving the pedagogical, professional, social, and personal abilities of teachers is the goal of this professional education program We collected data from a number of elementary school teachers who participated in the program for this research through a survey method, which is a quantitative approach This study involved one hundred elementary school teachers from various regions in Indonesia, The research used a questionnaire based on teacher competency standards and the goals of the professional education program The questionnaire consisted of several sections measuring teachers' perceptions of program effectiveness, the competency improvements they felt, and the program's impact on their teaching practices Descriptive and inferential statistical analysis was conducted to identify patterns and correlations in the collected data.